Crisis Prevention and Crisis Management : The Role of Regulatory Governance - Das, Udaibir (IMF Working Papers; Working Paper ;, 2002)
Good regulatory governance in the financial system is a critical component of financial stability. Research on the topic has not been very systematic and deep. This paper first defines four key components of regulatory governance-independence, accountability, transparency, and integrity. It explores the quality of regulatory governance based on the financial system evaluations under the Financial Sector Assessment Programs (FSAPs), which are the first and most comprehensive effort to analyze regulatory governance issues. In terms of independence, banking supervisors are ahead of the others, while securities regulators perform better on transparency. Insurance regulators are weak in all the regulatory governance components. On the whole, regulators still have a long way to go in terms of practicing good governance. The paper also discusses governance issues specific to crisis management and concludes with an agenda for further research.